2018
DOI: 10.1039/c8ra05384g
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of total glycosides from paeonies against neurotoxicity induced by strychnos alkaloids related to recovering the levels of neurotransmitters and neuroendocrine hormones in rat serum and brain

Abstract: Eight neurotransmitters and four neuroendocrine hormones in rat serum and brain were quantified to investigate the neuroprotective effect of total glycosides from paeony against neurotoxicity induced by strychnos alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Total paeony glycosides (TPGs) are the main active constituents in CS and total ligustici phenolic acids (TLPAs) are the major active components in CX. TPGs were reported to have a good effect on both cerebral ischemia and cardiac ischemia 16,17 . Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Total paeony glycosides (TPGs) are the main active constituents in CS and total ligustici phenolic acids (TLPAs) are the major active components in CX. TPGs were reported to have a good effect on both cerebral ischemia and cardiac ischemia 16,17 . Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…In rat models, PF administration attenuated cognitive deficits induced by scopolamine [51]. In addition, supplementation of PF significantly alleviated the neurotoxic effect through regulation of neurotransmitters and hormones in rat serum and brain [52]. According to previous studies, PF was detectable immediately in the cortex and hippocampus of rats after intravenous administration of Paeoniae Radix extract containing PF [53,54].…”
Section: Discussionmentioning
confidence: 87%
“…Another study detected seven neurotransmitters with the help of microdialysis coupled with hydrophilic interaction chromatography–tandem mass spectrometry (MD-HILIC–MS/MS) [ 57 ]. In the other studies, eight neurotransmitters were studied using LC-MS [ 58 , 59 ]. Only one study reported quantification of 10 neurotransmitters and their metabolites [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analytical method by Linjia Sun et al[59]:i. Chromatography technique: liquid chromatographytandem mass spectrometry (LC-MS/MS) method ii.…”
mentioning
confidence: 99%